Social Support and Level of Religiosity as Resilience Factors in Late Adult Widows - Munawwarah, Nadia Salsabila; Siti Nurjana Gani; Karmiyati, Diah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Widowed women who have just been abandoned by their partners need resilience. Resilience is a personality characteristic that a person can recover and adapt immediately after experiencing adversity. The resilience of a widow whose partner leaves her is influenced by several factors, including social support and religiosity. This research aims to find out whether social support and religiosity are factors that support the resilience of late adult widows. Systematic Literature Review (SLR) is the method applied in this research and results were found showing that social support and the level of religiosity play an important role in resilience mechanisms for dealing with the loss of a partner in late adulthood.